Can floral nectars reduce transmission of Leishmania? - Evan C. Palmer-Young; Ryan S. Schwarz; Yanping Chen; Jay D. Evans (Public Library of Science (PLoS), 2022)
Background Insect-vectored Leishmania are responsible for loss of more disability-adjusted life years than any parasite besides malaria. Elucidation of the environmental factors that affect parasite transmission by vectors is essential to develop sustainable methods of parasite control that do not have off-target effects on beneficial insects or environmental health. Many phytochemicals that inhibit growth of sand fly-vectored Leishmania-which have been exhaustively studied in the search for phytochemical-based drugs-are abundant in nectars, which provide sugar-based meals to infected sand flies. Principle findings In a quantitative meta-analysis, we compare inhibitory phytochemical concentrations for Leishmania to concentrations present in floral nectar and pollen. We show that nectar concentrations of several flowering plant species exceed those that inhibit growth of Leishmania cell cultures, suggesting an unexplored, landscape ecology-based approach to reduce Leishmania transmission. Significance If nectar compounds are as effective against parasites in the sand fly gut as predicted from experiments in vitro, strategic planting of antiparasitic phytochemical-rich floral resources or phytochemically enriched baits could reduce Leishmania loads in vectors. Such interventions could provide an environmentally friendly complement to existing means of disease control. Author summary Leishmania parasites infect over a million people each year-including over 200,000 infections with deadly visceral leishmaniasis-resulting in a greater health burden than any human parasite besides malaria. Leishmania infections of humans are transmitted by blood-feeding sand flies, which also consume floral nectar. Nectar contains many chemicals that inhibit Leishmania growth and are candidate treatments for infection of humans. However, these same compounds could also reduce infection in nectar-consuming sand flies. By combining existing data on the chemistry of nectar and sensitivity of Leishmania to plant compounds, we show that some floral nectars contain sufficient chemical concentrations to inhibit growth of insect-stage Leishmania. Our results suggest that consumption of these nectars could reduce parasite loads in sand flies and transmission of parasites to new human hosts. In contrast to insecticide-based methods of sand fly control, incorporation of antiparasitic nectar sources into landscapes and domestic settings could benefit public health without threatening beneficial insects. These findings suggest an unexplored, landscape-based approach to reduce transmission of a major neglected tropical disease worldwide.